Sustainable and environmental dyeing with MAUT method comparative selection of the dyeing recipe - ÖZOMAY, MERAL (My University, 2023)
The textile industry is one of the most complex sectors, in terms of the materials andchemical processes used from petroleum and the environmental degradation during its productionand disposal. It is therefore a sector looking for new possibilities and for more sustainable materialsand applications. One option is to use natural dyes, as they are considered biodegradable, do notpollute the environment, and have potential use for many sectors, including the fashion industry.In this study, Alanya silk was dyed by a natural dyeing method with crocus sativus, Helichrysumarenarium, and Glycyrrhiza glabra L., plants that grow in and around the Alanya region. Quercusaegilops L. grown in the region was preferred as mordant, a natural binder, and is one of the plantswith the highest tannin content, and it was used with a more environmentally friendly and sustainableapproach to increase the binding in natural dyeing instead of chemical mordants. The aim is to providean environmental and scientific contribution to the dyeing producers in this region. According to theMAUT (Multi-Attribute Utility Theory) method, the best dyes in terms of fastness and color efficiencywere determined as the dyes made with the Glycyrrhiza glabra L. plant.
Keywords: Tekstil Mühendisliği ve Teknolojisi; Tekstil Kimyası; Boya Terbiye Teknolojisi; Mühendislik ve Teknoloji; Textile Engineering and Technology; Textile Chemistry; Dye Finishing Technology; Engineering and Technology; Mühendislik, Bilişim ve Teknoloji (ENG); Malzeme Bilimi; MALZEME BİLİMİ, TEKSTİL; Engineering, Computing & Technology (ENG); MATERIALS SCIENCE; MATERIALS SCIENCE, TEXTILES